On the SARS-CoV-2 “Variolation Hypothesis”: No Association Between Viral Load of Index Cases and COVID-19 Severity of Secondary Cases - Trunfio, Mattia; Longo, Bianca Maria; Alladio, Francesca; Venuti, Francesco; Cerutti, Francesco; Ghisetti, Valeria; Bonora, Stefano; Di Perri, Giovanni; Calcagno, Andrea (Frontiers in Microbiology, 2021)
Background: Emerging evidence supports the “variolation hypothesis” in SARS-CoV-2, but the derivative idea that the viral load of index cases may predict disease severity in secondary cases could be unsubstantiated. We assessed whether the prevalence of symptomatic infections, hospitalization and deaths in household contacts of COVID-19 cases differed according to the SARS-CoV-2 PCR cycle threshold (Ct) from nasal-pharyngeal swab at diagnosis of linked index cases. Methods: Cross-sectional study on household contacts of COVID-19 cases randomly sampled from all the infections diagnosed in March at our Microbiology Laboratory (Amedeo di Savoia, Turin). Data were retrospectively collected by phone interviews and from the Piedmont regional platform for COVID-19 emergency. Index cases were classified as high (HVl) and low viral load (LVl) according to two exploratory cut-offs of RdRp gene Ct value. Secondary cases were defined as swab-confirmed or symptoms-based likely when not tested but presenting compatible clinical picture. Results: 132 index cases of whom 87.9% symptomatic and 289 household contacts were included. The latter were male and Caucasian in 44.3% and 95.8% of cases, with a median age of 34 years (19-57). 74 were swab-confirmed and other 28 were symptoms-based likely secondary cases. Considering both, the contacts of HVl and LVl did not differ in the prevalence of symptomatic infections nor COVID-19-related hospitalization and death. No difference in median Ct of index cases between symptomatic and asymptomatic, hospitalized and not hospitalized, or deceased and survived secondary cases was found. Negative findings were confirmed after adjusting for differences in time between COVID-19 onset and swab collection of index cases (median 5 days) and after removing pediatric secondary cases. Conclusions: The amount of SARS-CoV-2 of the source at diagnosis does not predict clinical outcomes of linked secondary cases. Considering the impelling release of assays for SARS-CoV-2 RNA exact quantification, these negative findings should inform clinical and public health strategies on how to interpret and use the data.